Rasionalisasi Mistisisme dalam Tradisi Baberten Sebagai Bentuk Menangkal Penyakit di Desa Pinggir Papas - Nadya Atika; Johny Alfian Khusyairi; Samidi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Pinggir Papas Village has attracted attention because it has succeeded in preventing COVID-19 cases while maintaining their local traditions. This happened during the COVID-19 pandemic which hit the whole world and amid globalization. To remain relevant within the framework of Islamic teachings and today's modern world, the baberten tradition, which is considered part of the local cultural heritage and beliefs, needs to be rationalized. This research aims to interpret the baberten tradition in Pinggir Papas Village, Kalianget District, as well as the rationalization of mysticism as a method of disease prevention. By using qualitative methods and an ethnographic approach, the data and research data sources come from the baberten tradition and sources as well as baberten tradition activities. The baberten ritual is performed twice a year, with three different processions. This ritual has certain goals and symbols. Three main components are involved in value rationalization, (1) offerings, (2) reading prayers, mantras and Surah At-Taubah, and (3) night journey. The research findings show that rationalizing the values ​​of the baberten tradition can give rise to a more reasonable understanding of the values ​​of mysticism and allow baberten to continue without eliminating the religious principles adhered to by the residents of Pinggir Papas Village. Thus, this research provides a foundation for the sustainability and maintenance of cultural heritage in Pinggir Papas Village and makes a significant contribution to our understanding of the dynamics between local traditions, Islamic religious teachings, and contemporary challenges such as the COVID-19 pandemic.